Counseling About Hospital Health Promotion For Employees In Malahayati Islamic Hospital - Cut Roza Asminanda; Balqis Nurmauli Damanik; Syahferi Anwar; Tasya Aurelia; Amandha Asri Sirait; Emmy Ramadhani; Ilham Habibi; Hafiz Muamar; Siska Siska; Nurdina Fitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Hospitals as health service institutions have a strategic role in providing quality services to the community. Fulfilling the accreditation standards set by the Ministry of Health is an inevitable effort to ensure that the services provided by hospitals meet high criteria. In facing the era of development of health science and technology, it is important for hospital employees to not only understand, but also be able to implement health promotion concepts in accordance with the latest accreditation standards.